Chrysomya megacephala larvae feeding favourably influences manure microbiome, heavy metal stability and greenhouse gas emissions. Issue 3 (14th March 2018) - Wang, Xiaoyun; Wang, Wanqiang; Gao, Qiao; Wang, Xiaoping; Lei, Chaoliang; Zhu, Fen
Summary: Chrysomya megacephala is a saprophagous fly whose larvae can compost manure and yield biomass and bio‐fertilizer simultaneously. However, there are concerns for the safety of the composting system, that is risk of diseases spread by way of manure pathogens, residue of harmful metals and emission of greenhouse gases. Microbiota analysis and heavy metal speciation by European Communities Bureau of Reference were evaluated in raw, C. megacephala ‐composted and natural stacked swine manure to survey pathogenic bacterial changes and mobility of lead and cadmium in manure after C. megacephala feeding; the emission rate of CH4 and N2 O from manure during C. megacephala composting and natural stacking was also measured. C. megacephala composting altered manure microbiota, reduced the risk of pathogenic bacteria and maintained the stability, and microbiota changes might be associated with heavy metal fractions, especially in Pseudomonas and Prevotella . In addition, C. megacephala ‐composting significantly reduced the emission rate of CH4 and N2 O in comparing with natural stacking situation and the first two days should be the crucial period for CH4 and N2 O emission measurement for manure treatment by C. megacephala . Moreover, OTU26 and Betaproteobacteria were changed after C. megacephala composting which might play a role in emission of CH4 and N2 O, respectively. Abstract : Chrysomya megacephala ‐composting altered manure microbiota, maintained heavy metal stability and facilitated greenhouse gas emission management. The latter two effects might have connections with manure microbiota changes during the composting process.